Transformational Leadership, Organizational Culture, and Religious Values Impact on Employee Performance - R Taufiq Nur Muftiyanto; Dodik Jatmika (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The hospitality industry in Sumedang faces challenges such as low hotel occupancy and declining restaurant revenues, highlighting the need for effective leadership and a strong organizational culture to improve employee performance. This study aims to examine the influence of transformational leadership on employee performance through organizational culture, with religious values as a moderating factor. A quantitative approach was employed, collecting data from 115 supervisory and managerial employees using a five-point Likert scale questionnaire. Purposive sampling ensured participants were permanent employees with at least one year of experience. Data were analyzed using structural equation modeling (SEM) via SmartPLS. The results indicate that transformational leadership positively shapes organizational culture, which in turn enhances employee performance. Moreover, religious values strengthen the relationship between organizational culture and performance by fostering ethical behavior. In conclusion, promoting transformational leadership and a supportive organizational culture, aligned with religious values, can effectively enhance employee performance and provide practical strategies for improving service quality in Sumedang’s hospitality sector.